Weight loss and mortality in people living with HIV: Systematic Review Protocol and Meta-analysis (Principles and Practice of Clinical Research, 2021)
Introduction: At the time of the first reported cases of human immunodeficiency virus (HIV) infection, people living with HIV (PLHIV) experienced weight loss. Highly active antiretroviral therapy (HAART) has dramatically changed their weight loss condition to ideal weight, overweight, and even obesity. However, there is a percentage of PLHIV that still presents weight loss, which is an independent predictor of mortality, even on HAART. Therefore, we sought to answer whether the hospitalized PLHIV on HAART, with weight loss, have higher mortality rates compared to hospitalized PLHIV on HAART, without weight loss.Method: This is a systematic review and meta-analysis study protocol for observational studies. A systematic literature search will be performed in the MEDLINE databases via PubMed, Embase, and LILACS, using the descriptors: HIV; highly active antiretroviral therapy; weight loss; hospitalization; malnutrition; thinness; HIV wasting syndrome; body weight and mortality. The detailed study protocol was registered in the International Prospective Registry of Systematic Reviews (PROSPERO) under the number CRD42020191246. The searching process will be carried out by two reviewers, independently, and segmented into phases: Identification, Screening, Eligibility, and Selection. To analyze the methodological quality and risk of bias, the Joanna Briggs Institute (JBI) critical assessment tool for cohort studies will be used. Heterogeneity among studies will be evaluated using the Cochran's Q test and Higgins and Thompson I² statistics. Egger and Begg tests will be used to assess publication bias. The systematic review will be conducted according to the checklist of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).Results: It is expected to produce consistent results, with a high level of scientific evidence, related to the clinical outcomes of hospitalized PLHIV on HAART with weight loss, contributing to relevant knowledge on the subject. Conclusion: From a public health perspective, the knowledge obtained is essential to plan and implement strategies to reduce mortality in PLHIV/AIDS, especially considering the high cost of treating PLHIV in Brazil and its increase if people are hospitalized. Thus, knowing whether hospitalized PLHIV on HAART, with weight loss, have higher mortality rates than those without weight loss, will contribute to new and relevant knowledge regarding a serious public health problem, and may guide public health care and policies.Keywords: HIV; Highly Active Antiretroviral Therapy; Weight loss; Hospitalization; Malnutrition; Consumptive Syndrome; Mortality.